Study the Hemoglobin Electrophoresis Patterns in two Populations from Salah - addin Province - Iraq - Wajdi Sabeeh Sadeq (Tikrit Journal of Pure Science)
The early identification of some clinically significant hemoglobinopathies and precise differentiation of hemoglobin variants are important to provide early comprehensive medical care to prevent some serious complications, assess prognosis and offer genetic counseling.